The relationship of feeding complementary food for breast milk (mp asi) to children aged 0-24 months with the incidence of diarrhea in the work area of Pematang Raya Puskesmas, Simalungun district - Mustarduddin; Almazhia Mahliza (Institute of Computer Science (IOCS), 2022)
Diarrheal disease in Indonesia is a major public health problem. This is due to the high diarrhea morbidity rate which causes many deaths, especially in toddlers. In Indonesia it was reported as a whole in 2006 it was estimated that diarrhea morbidity rates increased by 423 per 1000 population at all ages with a total of 10,980 cases and 277 deaths under five. In 2008, in Indonesia there were around 40 million episodes of diarrhea in toddlers per year with the death of 200,000-400,000 toddlers (Soebagyo, 2008). The purpose of this study was to determine the relationship between the provision of complementary feeding (MP ASI) in children aged 0-24 months with the incidence of diarrhea in the working area of the Pematang Raya Health Center, Simalungun Regency in 2017. The research design was an observational study using a comparative case design. (case control study). Based on the results of bivariate analysis with the chi-square statistical test on the types of complementary foods, it shows that p value = 0.025 where the p count is greater than the p table of 0.05 (p> 0.05), this indicates that there is a relationship between the types of complementary foods in children aged 0-24 months with the incidence of diarrhea, with an OR value of 0.359. It is hoped that it will be used as input material in planning diarrhea disease prevention policies, preparing health plans, and evaluating health programs, especially in preventing diarrheal diseases related to complementary feeding of breast milk